Answer:
1 ClO-(aq) + 1 I-(aq) ---> 1 Cl -(aq) + 1 IO-(aq).
Explanation:
1. ClO-(aq) + H2O(l) <=> HClO(aq) + OH-(aq)
2. I-(aq) + HClO(aq) <=> HIO(aq) + Cl-(aq)
3. OH-(aq) + HIO(aq) => H2O(l) + IO-(aq)
Adding all the 3 equations together gives and it gives:
ClO-(aq) + H2O(l) + I-(aq) + HClO(aq) + OH -(aq) + HIO(aq)
---> HClO(aq) + OH-(aq) + HIO(aq) + Cl -(aq) + H2O(l) + IO-(aq)
Deleting the same species on both sides of the equation gives:
1 ClO-(aq) + 1 I-(aq) ---> 1 Cl -(aq) + 1 IO-(aq)
The overall equation:
1 ClO-(aq) + 1 I-(aq) ---> 1 Cl -(aq) + 1 IO-(aq)